(untitled) (Journal of Psychiatrists’ Association of Nepal, 2025)
Background: Depression is one of the common psychiatric comorbidity in individuals with epilepsy and is associated with poor quality of life, increased suicidal ideation, social handicaps and increased morbidity. Epilepsy is a highly stigmatized condition even today leading to discrimination and marginalization with significant social limitations. The objective of the present study was to determine the prevalence of depression and perceived stigma in individuals with epilepsy along with identification of factors associated with it. Methods: The study employed a descriptive cross-sectional observational design and was conducted among patients with epilepsy attending the Psychiatry and Internal Medicine outpatient departments (OPDs) of Devdaha Medical College over a 6-month period, from 1st Jan 2025 to 31st June 2025. Ethical approval was obtained from the Institutional Review Committee of the same institute (approval number: 23/2024). A convenience sampling technique was utilized. The Epilepsy Stigma Scale was administered to assess perceived stigma. Point estimates were calculated with a 95% Confidence Interval. Results: Out of 195 total participants, 102 (52.2%) were males. The median age was 32 years. Depression was present in 92 (48.2%) patients, most of them had moderate depresssion (84.23%). Perceived stigma was present in 129(66.2%) patients with epilepsy according to epilepsy stigma scale where mean score was 4.83±2.07. Using the Chi-square test, significant associations were found between depression and several variables including gender, type of family, family income, occupation, duration of epilepsy, and perceived stigma (p < 0.05). Conclusion: The prevalence of depression was almost half among individuals with epilepsy, and more than two-thirds experienced perceived stigma. These findings indicate the need to integrate mental health screening and support into epilepsy care in Nepal.